Maintaining Legitimacy as a Crisis Response Strategy – A Qualitative Analysis of Nottingham Business School’s Crisis Response during Covid-19 - Hafeez, Dania (2022)
Legitimacy determines an organisation’s purpose and reason for existence. In times of crisis, an organisation’s long term survival may come under threat, therefore, it is important for organisations to address and maintain their legitimacy as part of their crisis response. This study uses a qualitative lens to evaluate the role of legitimacy in Nottingham Business School’s crisis response strategy towards the Covid-19 pandemic and explores student feelings and perceptions about the actions taken. The study utilises one on one interviews with students and staff members from the Business School along with secondary data analysis of the university’s communication archive to study legitimacy as part of the Business School’s crisis response strategy. The study discovered communication and consultation with key stakeholders, providing students a learning experience that matches their expectations and supporting the university’s decisions backed by authoritative institutions as the main determinants of legitimacy during the pandemic. The study also highlights that students develop trust in the actions taken by the Business School when there is clear and honest communication and when the Business School is able to match their expectations of the learning and student experience in a university setting.